USO DO TERRITÓRIO NO VALE DO SÃO FRANCISCO: SISTEMA TÉCNICO AGRÍCOLA DA FRUTICULTURA IRRIGADA - Ramos, Soraia de Fátima (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2013)
The article summarizes aspects of Milton Santos' theoretical and methodological guidance with the presentation of the issue of master's thesis, conducted at the Department of Geography, University of São Paulo between 1998 and 2001. The purpose is to indicate the theoretical reference that supported the research, which aimed to investigate new uses of the territory in Submédio São Francisco Valley, northeast region of Brazil. Since mid-1970s, with the selective expansion of the technical scientific and informational milieu across the country, constitutes in part of the semi arid portion, in the municipalities of Petrolina (Pernambuco) and Juazeiro (Bahia), the agricultural technical system of irrigated fruit farming to export. The dynamics of the regional territory – objects and actions – was examined in the light of the modernization and specialization of production in field.